2014
DOI: 10.1177/0300060514549782
|View full text |Cite
|
Sign up to set email alerts
|

Early haemoperfusion with continuous venovenous haemofiltration improves survival of acute paraquat-poisoned patients

Abstract: Objective: To determine whether haemoperfusion (HP) with continuous venovenous haemofiltration (CVVH) improves the survival of patients with acute paraquat poisoning, compared with those treated using HP alone. Methods: Medical records of patients with acute paraquat poisoning were analysed. Patients were randomised to undergo HP or HP þ CVVH within 24 h of paraquat ingestion. Mortality rate, survival duration and cause of death were recorded. Results: There were no significant differences in mortality rate be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 19 publications
0
18
0
2
Order By: Relevance
“…In some other observational studies, the study by Jie Gao et al states that prolonged MP therapy after pulse treatment can reduce the mortality of moderate-to-severe PQ poisoning patients (Gao et al, 2017). Early hemoperfusion may improve the survival chances of PQ poisoning patients, as was confirmed in three studies (Gao et al, 2015;Hsu et al, 2012;Wang et al, 2017). A multivariate logistic regression analysis showed that the addition of vitamin C to the treatment was significantly associated with increased survival of the patients in the study by Moon and Chun (2011).…”
Section: Hypoxiamentioning
confidence: 77%
“…In some other observational studies, the study by Jie Gao et al states that prolonged MP therapy after pulse treatment can reduce the mortality of moderate-to-severe PQ poisoning patients (Gao et al, 2017). Early hemoperfusion may improve the survival chances of PQ poisoning patients, as was confirmed in three studies (Gao et al, 2015;Hsu et al, 2012;Wang et al, 2017). A multivariate logistic regression analysis showed that the addition of vitamin C to the treatment was significantly associated with increased survival of the patients in the study by Moon and Chun (2011).…”
Section: Hypoxiamentioning
confidence: 77%
“…The survival advantage of early haemoperfusion following paraquat exposure has been addressed in various studies. [5], [6] 8 patients received Haemoperfusion while 14 patients received early Haemodialysis for toxin removal.2 patients died before extracorporeal therapy could be initiated. Pulse steroids and cyclophosphamide are generally given to reduce the inflammation process in the lung following paraquat ingestion.…”
Section: Discussionmentioning
confidence: 99%
“…[13–17] Compared to HP, continuous venovenous hemofiltration (CVVH), the most commonly used type of continuous renal replacement therapy, possesses diffusive, convective, and adsorptive functions. [18,19] Theoretically, these features of CVVH cannot only help remove the toxin from the blood, but can also help clear the large number of inflammatory mediators and inflammatory factors produced upon PQ poisoning. However, although CVVH has already been applied for the treatment of PQ poisoning in clinical practice, its efficacy remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…However, although CVVH has already been applied for the treatment of PQ poisoning in clinical practice, its efficacy remains controversial. [9,1821] Therefore, in the present study, we conducted a meta-analysis of reported randomized controlled trials (RCTs) to further clarify the efficacy of CVVH in the treatment of PQ poisoning.…”
Section: Introductionmentioning
confidence: 99%